2011
DOI: 10.1590/s0103-90162011000500006
|View full text |Cite
|
Sign up to set email alerts
|

Trifoliata hybrids rootstocks for 'Lane Late' navel orange in Spain

Abstract: Yield was weighed during the first nine harvests, fruit quality was determined in the last three. Pre-harvest fruit-drop was controlled for the 4 th until 9 th harvests. The trees of 'Lane Late' navel budded on Cleopatra mandarin were the tallest (2.5 m) and F&A 418 (1.6 m) the shortest of all rootstocks tested. Trees on 030131 hybrid and Carrizo citrange rootstocks had the highest mean yield (81.2 and 80.3 kg per tree per year respectively), while trees on F&A 418 produced the lowest mean yield (22.3 kg per t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
12
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 6 publications
5
12
1
1
Order By: Relevance
“…At the far end, the low yield of trees on Cleopatra mandarin means very poor yield efficiency. In 'Lane late' trees, the best yield efficiency corresponded to the trees on C. macrophylla, and the lowest yield-efficient trees were those grafted onto Gou Tou, Cleopatra mandarin and FA 418, while C. volkameriana offered an intermediate yield efficiency [73,77]. Similar results have been reported on 'Navelina' orange, who found that the trees on C. volkameriana had similar yield efficiency, but lower yield efficiency on Cleopatra mandarin [57].…”
Section: Yield and Yield Efficiencysupporting
confidence: 69%
See 4 more Smart Citations
“…At the far end, the low yield of trees on Cleopatra mandarin means very poor yield efficiency. In 'Lane late' trees, the best yield efficiency corresponded to the trees on C. macrophylla, and the lowest yield-efficient trees were those grafted onto Gou Tou, Cleopatra mandarin and FA 418, while C. volkameriana offered an intermediate yield efficiency [73,77]. Similar results have been reported on 'Navelina' orange, who found that the trees on C. volkameriana had similar yield efficiency, but lower yield efficiency on Cleopatra mandarin [57].…”
Section: Yield and Yield Efficiencysupporting
confidence: 69%
“…This tendency has also been observed in 'Navelina' orange trees grafted onto C. volkameriana rootstocks [57]. Some new rootstocks obtained in the breeding programme carried out at the IVIA, in particular rootstocks FA 5 and FA 13, presented an intermediate size [57], while smaller trees were grated onto FA 418 [77]. In mandarine scions, C. volkameriana also conferred the largest size to 'Clausellina' trees compared with Carrizo citrange [78], the most commonly used rootstock in Spain.…”
Section: Tree Vegetative Growthsupporting
confidence: 52%
See 3 more Smart Citations